Experience of Antibiotic Use and Resistance Among Pharmacy Students in the University of Kerbala (Journal of Basic and Applied Research in Biomedicine, 2022)
Introduction: Antibiotic resistance occurs when bacteria develop the ability to defeat the drugs designed to kill them. Antibiotics dispensing without prescription, misuse of antibiotics are considered as a major cause of antibiotic resistance. Antimicrobial resistance causes extra health care cost and leads to loss of productivity; also patients with resistant infections are more expensive and difficult to treat. Many strategies and steps can be taken at all levels of society to reduce the impact and limit the spread of resistance. The pharmacist has effective role in averting antibiotic resistance. Methodology: A questioner form was designed to assess student’s knowledge, attitude and perception about antibiotic use and resistance, 146 pharmacy students from the fourth stage and fifth stage in the University of Kerbala, were selected randomly. Result: A total number of 146 students, (70 from the fourth stage and 76 from the fifth stage) were participated in this study of both sexes (30 male: 116 female). About 82% of students understand what the antibiotic resistance term mean. 87% of students knew that antibiotics shouldn’t be used for common cold. 84% of students did not stop taking antibiotics until taken all of the antibiotics as directed. 34% of students usually consult a doctor before starting an antibiotic. Less than 23% of students did not stop taking antibiotic when any side effect appears. Conclusion: Based on results obtained in this study that done in Kerbala University / College of Pharmacy it has been concluded that students were of high level in knowledge and perception about antibiotics use and resistance, but the students were of lower level in attitudes, lower percent of student have good attitude toward antibiotics use.